Pentru ortodoxie curse de toată mîna (Confluenţe Bibliologice, 2025)
The author gloriﬁes authentic Christianity teaches that Lord Jesus Christ left. She called us to be on guard against false prophets who seek by all means to lead people astray from the essential truths of God word and to deviate from the true faith transmitted by words and false ideas.